Chapter Plasma Polymerization for Tissue Engineering Purposes - Morent, Rino (InTechOpen, 2018)
The ability of non-equilibrium plasmas to modify surfaces has been known for many years. And a promising way to perform surface modifications without altering the bulk properties is plasma polymerization since this technique is versatile and can be applied to a wide range of materials. Plasma polymer films usually show good biocompatibility when compared to classical biomaterials. The possible biomedical use of plasma polymers motivates the study of their behavior during storage and in aqueous environment. Therefore, it is of major importance to understand the change of properties of these plasma polymers over time and when in contact with certain fluids. Recently, plasma polymer gradients (surfaces that display a change in at least one physicochemical property over distance) have attracted significant attention from the biomedical filed where the interaction of cells with a material surface is of major interest. This chapter discusses biomaterial functionalization via plasma polymerization focusing on their use in the biomedical field as well as their aging and stability behaviors. Plasma polymer gradients as valuable tools to investigate cell-surface interactions will also be reviewed.